1997
DOI: 10.1161/01.atv.17.8.1539
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor VII and the Risk of Coronary Heart Disease in Healthy Men

Abstract: Numerous investigations have demonstrated the role of thrombus formation in the pathogenesis of coronary heart disease (CHD). A tendency to thrombosis may also be indicated by elevated levels of coagulation factor VII clotting activity (FVIIc). Significant associations of FVIIc with increased coronary risk, however, have been found only in the Northwick Park Heart Study. Here we present the results of the 8-year follow-up of FVIIc measurements in 2780 healthy men of the Prospective Cardiovascular Münster study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(91 citation statements)
references
References 21 publications
5
84
1
1
Order By: Relevance
“…Still, our findings indicate a possible association between IRS and increased endothelial cell activation, namely mediated by sICAM and sVCAM levels, which could also mediate the development of atherosclerosis and coronary heart disease in this group. FVIIa is produced after activation of FVII by tissue factor and is a marker of the activation status of this tissue factor coagulation pathway when detected in vivo; increased levels of FVIIc also have been shown to be a risk factor for coronary heart disease (30). In this study, increased FVIIc and FVIIa levels were found in both men and women with IRS, indicating a possible procoagulant status associated with IRS.…”
Section: Relationships Between Irs Components and Inflammation And Cosupporting
confidence: 48%
“…Still, our findings indicate a possible association between IRS and increased endothelial cell activation, namely mediated by sICAM and sVCAM levels, which could also mediate the development of atherosclerosis and coronary heart disease in this group. FVIIa is produced after activation of FVII by tissue factor and is a marker of the activation status of this tissue factor coagulation pathway when detected in vivo; increased levels of FVIIc also have been shown to be a risk factor for coronary heart disease (30). In this study, increased FVIIc and FVIIa levels were found in both men and women with IRS, indicating a possible procoagulant status associated with IRS.…”
Section: Relationships Between Irs Components and Inflammation And Cosupporting
confidence: 48%
“…For example, the ARIC study 18 did not find factor VII associated with CHD events. In contrast, the Northwick Park Heart Study 21 and Prospective Cardiovascular Munster (PROCAM) study 22 reported a strong positive association between factor VII and CHD events. Nonetheless, most studies have shown that factor VII is not associated with all events of stroke 4,5 and IS.…”
Section: Discussionmentioning
confidence: 94%
“…The increase of coagulant factor VII observed in this review may be due to chance but might indicate an adverse effect of n-3 PUFA. This requires further research as increased plasma activity of factor VIIc is associated with CHD risk factors such as hypertriacylglycerolaemia, reduced glucose tolerance, overweight and hyperinsulinaemia, but may also be an independent risk factor for CHD [66][67][68], and higher levels were observed in healthy subjects with coronary events [69]. However, the independent association with CHD was not shown in another cohort study [70].…”
Section: Discussionmentioning
confidence: 96%